Comparative in vitro activities of azlocillin-cefotaxime and azlocillin-tobramycin combinations against blood and multi-drug resistant bacterial isolates. - Fass, R J (1982)
The in vitro activities of azlocillin and cefotaxime in combination and of azlocillin and tobramycin in combination against 100 blood isolates and 50 multidrug-resistant isolates were compared. With both combinations, antibacterial spectrums were complementary. Although synergy against individual strains was infrequently observed (except for azlocillin-cefotaxime against Streptococcus faecalis and azlocillin-tobramycin against Pseudomonas aeruginosa), 97% of blood isolates and 76% of multidrug-resistant isolates were susceptible to azlocillin-cefotaxime, and 94% of blood isolates and 36% of multidrug-resistant isolates were susceptible to azlocyclin-tobramycin.